Cultura tributaria e informalidad de los comerciantes del centro poblado San Gabriel de Varadero distrito de Balsapuerto, 2022 - Da Cruz Olortegui, Jason Gabriel (2023)
The purpose of this study is to establish the relationship between tax culture and informality in the merchants of the San Gabriel De Varadero, Balsapuerto District, 2022. It is a quantitative approach, of a descriptive correlational and non-experimental design, the population and sample of 20 merchants. It was obtained 0.773 as a result of very high correlation and a sigma (bilateral) of 0.01: the calculated p value is less than 0.05. Therefore, the Ha is accepted. As the value obtained accepts the Ha, then it was concluded that the hypothesis is approved because it is positive and significant between variable 1 and 2.